Water-Soluble C60 Protects Against Bleomycin-Induced Pulmonary Fibrosis in Mice - Dong R; Liu M; Huang XX; Liu Z; Jiang DY; Xiao HJ; Geng J; Ren YH; Dai HP (International Journal of Nanomedicine, 2020)
Run Dong,1,2,* Min Liu,3,* Xiao-Xi Huang,4 Zheng Liu,4 Ding-Yuan Jiang,5 Hui-Juan Xiao,1 Jing Geng,5 Yan-Hong Ren,5 Hua-Ping Dai5 1Beijing Key Laboratory of Respiratory and Pulmonary Circulation Disorders, Department of Respiratory Medicine, Capital Medical University, Beijing, People’s Republic of China; 2Department of Respiratory Medicine, Zhengzhou Central Hospital, Zhengzhou, People’s Republic of China; 3Department of Radiology, China-Japan Friendship Hospital, Beijing, People’s Republic of China; 4Beijing Key Laboratory of Respiratory and Pulmonary Circulation Disorders, Department of Medical Research, Beijing Chao-Yang Hospital, Capital Medical University, Beijing, People’s Republic of China; 5Department of Pulmonary and Critical Care Medicine, Center of Respiratory Medicine, China-Japan Friendship Hospital; National Clinical Research Center for Respiratory Diseases; Capital Medical University, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hua-Ping DaiDepartment of Pulmonary and Critical Care Medicine, China-Japan Friendship Hospital, Beijing 100029, People’s Republic of ChinaEmail daihuaping@ccmu.edu.cnBackground: Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive, fibrotic interstitial pneumonia. And, oxidation/antioxidant imbalance plays an important role in the progress of IPF. Fullerene is considered to be a novel “structural” antioxidant. This study aimed to explore if water-soluble C60 (C60(OH)22) can exhibit antifibrotic activity in its antioxidant role.Methods: Healthy C57BL/6J mice were randomly grouped and induced pulmonary fibrosis by intratracheal injection of bleomycin.Results: The survival rate of mice was observed and found that 10mg/kg was the optimal dose of water-soluble C60 for pulmonary fibrosis. We observed that water-soluble C60 can alleviate the severity of pulmonary fibrosis by observing the chest computed tomography, pulmonary pathology, and content of collagen, alpha smooth muscle actin and fibronectin in lung. Compared with bleomycin group, ROS, the content of TNF-α in BALF, and the number of fibroblasts was significantly decreased and the number of type Ⅱ alveolar epithelial cells was increased after treatment with C60.Conclusion: Therefore, thanks to its powerful antioxidant action, water-soluble C60 can reduce the severity of pulmonary fibrosis induced by bleomycin in mice.Keywords: pulmonary fibrosis, bleomycin, water-soluble C60, mice